2020
DOI: 10.1111/eci.13204
|View full text |Cite
|
Sign up to set email alerts
|

The impact of DRP1 on myocardial fibrosis in the obese minipig

Abstract: Background The heart is a highly oxidative tissue, thus mitochondria play a major role in maintaining optimal cardiac function. Our previous study established a dietary‐induced obese minipig with cardiac fibrosis. The aim of this study was to elucidate the role of mitochondrial dynamics in cardiac fibrosis of obese minipigs. Design Four‐month‐old Lee‐Sung minipigs were randomly divided into two groups: a control group (C) and an obese group (O) by feeding a control diet or a high‐fat diet (HFD) for 6 months. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…However, dysregulated mitochondrial dynamics, including enhanced mitochondrial fission, can lead to the reprogramming of energy metabolism, mitochondrial damage, and even disease (Westermann, 2010;Youle and van der Bliek, 2012;Willems et al, 2015). These effects have been implicated in organ fibrosis and associated with different types of fibroblasts, and the connection between mitochondrial fission and fibrotic events is further supported by both in vitro and in vivo evidence (Zhang et al, 2015(Zhang et al, , 2020Tian et al, 2018;Tseng et al, 2019;Chen et al, 2020a;Wang et al, 2020e).…”
Section: Figure 3 | Reducing the Cardiac Fibroblasts (Cf) Glycolytic Flux May Be Important For Mitochondrial Fission Inhibition-induced Smentioning
confidence: 99%
See 1 more Smart Citation
“…However, dysregulated mitochondrial dynamics, including enhanced mitochondrial fission, can lead to the reprogramming of energy metabolism, mitochondrial damage, and even disease (Westermann, 2010;Youle and van der Bliek, 2012;Willems et al, 2015). These effects have been implicated in organ fibrosis and associated with different types of fibroblasts, and the connection between mitochondrial fission and fibrotic events is further supported by both in vitro and in vivo evidence (Zhang et al, 2015(Zhang et al, , 2020Tian et al, 2018;Tseng et al, 2019;Chen et al, 2020a;Wang et al, 2020e).…”
Section: Figure 3 | Reducing the Cardiac Fibroblasts (Cf) Glycolytic Flux May Be Important For Mitochondrial Fission Inhibition-induced Smentioning
confidence: 99%
“…However, these two models were not classical profibrotic CF models. Mitochondrial fission was also shown to play a progressive role in obesity-induced cardiac fibrosis in obese minipigs (Chen et al, 2020a); as with the above-mentioned studies, the authors used the H9C2 cardiomyocyte line and not CF as the in vitro model, which could not recapitulate the importance of mitochondrial fission in CF. According to our findings, mdivi-1 could reduce TGF-β1-induced mitochondrial fission, as well as activation, proliferation, collagen deposition, and migration of cultured CF, which was consistent with the conclusions of the aforementioned studies.…”
Section: Figure 3 | Reducing the Cardiac Fibroblasts (Cf) Glycolytic Flux May Be Important For Mitochondrial Fission Inhibition-induced Smentioning
confidence: 99%
“…The significantly downregulated expressions of MFN2 and OPA1, but not MFN1, were the shared alterations in the heart, kidney, liver, spleen, and skeletal muscle of HFD-fed mice. The results are consistent with most previous studies on mitochondrial fusion protein changes in the obesity or metabolic disease, which proved that MFN2 and/or OPA1 were significantly reduced in the tissue or cell of skeletal muscle, ( 33 39 ) fat, ( 40 , 41 ) hypothalamus, ( 42 ) kidney, ( 43 ) heart, ( 44 47 ) liver, ( 48 ) etc. On the contrary, a few studies reported that MFN2 was increased in the heart and liver, ( 49 , 50 ) unchanged in the fat, ( 50 ) skeletal muscle or cell of metabolic disease.…”
Section: Discussionsupporting
confidence: 92%
“…Through in vitro and in vivo experiments and pathological/molecular biological detection methods, we verified the mechanism of GN improving myocardial injury and cardiomyocyte activity through TMBIM6-related mitophagy. We mainly verified three characteristics of the drug action of GN (GN combined with MET): first, GN can improve myocardial fibrosis and myocardial injury and is closely related to the regulation of mitochondrial structure and function; second, GN can improve mitophagy through TMBIM6, regulate the redox balance under high glucose stimulation, and improve the activity of cardiomyocytes under high glucose stimulation; third, the combined treatment of GN and MET can improve cardiomyocyte activity, which may be related to the [41,42]. The cytokines that induce heart remodeling and dysfunction can be derived from the heart, including cardiomyocytes, coronary microvascular endothelial cells, cardiac fibroblasts, and immune cells [43,44].…”
Section: Discussionmentioning
confidence: 99%